Comparing peak and submaximal cardiorespiratory responses during field walking tests with incremental cycle ergometry in COPD - Hill, Kylie; Dolmage, T.; Woon, L.; Coutts, D.; Goldstein, R.; Brooks, D. (Wiley-Blackwell Publishing Asia, 2012)
Background and objective: Field and laboratory-based tests are used to measure exercise capacity in people with COPD. A comparison of the cardiorespiratory responses to field tests, referenced to a laboratory test, is needed to appreciate the relative physiological demands. We sought to compare peak and submaximal cardiorespiratory responses to the 6-min walk test, incremental shuttle walk test and endurance shuttle walk test with a ramp cycle ergometer test (CET) in patients with COPD. Methods: Twenty-four participants (FEV1 50 ± 14%; 66.5 ± 7.7 years; 15 men) completed four sessions, separated by ≥24 h. During an individual session, participants completed either two 6-min walk tests, incremental shuttle walk tests, endurance shuttle walk tests using standardized protocols, or a single CET, wearing a portable gas analysis unit (Cosmed K4b2) which included measures of heart rate and arterial oxygen saturation (SpO2). Results: Between tests, no difference was observed in the peak rate of oxygen uptake (F3,69 = 1.2; P = 0.31), end-test heart rate (F2,50 = 0.6; P = 0.58) or tidal volume (F3,69 = 1.5; P = 0.21). Compared with all walking tests, the CET elicited a higher peak rate of carbon dioxide output (1173 ± 350 mL/min; F3,62 = 4.8; P = 0.006), minute ventilation (48 ± 17 L/min; F3,69 = 10.2; P < 0.001) and a higher end-test SpO2 (95 ± 4%; F3,63 = 24.9; P < 0.001). Conclusions: In patients with moderate COPD, field walking tests elicited a similar peak rate of oxygen uptake and heart rate as a CET, demonstrating that both self- and externally paced walking tests progress to high intensities.